From resurrection to rehabilitation: Laurence Sterne and his readers in Soviet Russia (1919-1941) - Budrin, P (2020)
This thesis examines the 1920s and 1930s as the critical juncture in the rich history of the Russian reception of writings and personality of Laurence Sterne. This study introduces a range of previously unpublished archival materials, including hitherto unknown Russian translations of Tristram Shandy and A Sentimental Journey, essays, illustrations, and private letters. Through a close examination of archival history, it reveals how the eccentric eighteenth-century Yorkshire clergyman was read, translated, and gained admirers within an increasingly totalitarian society. The Soviet state had no political interest in Sterne. What drove this writer’s intensified popularity were individuals who appreciated Sterne’s works and were willing to share their admiration with others.